Gross Morphology and Biometry of the Testes of Tom Cat - Maitri J. Patel; K. M. Panchal; Pradnya Gaikwad; Harish P. Gori (Indian Journal of Veterinary Anatomy, 2024)
The present research work was carried out on testes procured from six healthy adult male cats brought for castration/neutering at Veterinary Clinical Complex as well as Department of Veterinary Surgery & Radiology, College of Veterinary science and Animal Husbandry, Kamdhenu University, Anand, Gujarat. The testes were paired gonads with reddish white color and oval shape. They were oriented obliquely within the scrotum. The long axis of each testis was dorso-caudal to the long axis of animal's body with dorso-laterally located epididymis. The left testis was caudal as compared to the right testis. The mean weight of left and right testis was 1.94±0.19 g and 1.88±0.19 g, respectively with gonadosomatic index 0.05±0.004% and 0.049±0.004%, respectively. The mean length, width and thickness of left and right testis was 18.00±0.58 mm and 16.83±0.54 mm; 13.67±0.71 mm and 13.17±0.79 mm and 11.50±0.56 mm and 10.83±0.48 mm, respectively. The left testis was non significantly larger than right testis.